Medicinska fakulteta Univerze v Mariboru: Znanstvena monografija o ustanovitvi (University of Maribor Press, 2022)
Faculty of Medicine of the University of Maribor: Scientific monograph on the establishment. In the existent scientific monograph we substantiate all reasons which contributed to the emergence of the second medical faculty in Slovenia. The MF UM has educated in its 16-year-activity approximately 1,000 physicians and has thereby partly helped to reduce gaps in the shortage of medical staff in Slovenia, for the comparable data on the number of physicians per 100,000 inhabitants still ran k Slovenia in the lower third among the European countries. The development of the faculty has consequently helped to the development of the entire healthcare in NE Slovenia, the formation of the MF UM was also a precondition for the development of the General Hospital Maribor into the University Clinical Centre Maribor. In the monograph we show the development of research and journalistic work which has developed rapidly in the recent 15 years, simultaneously with the development of the faculty. The scientific monograph does not show only the MF UM formation, but also indicates further development of the MF UM in the sense of two new programmes: Dental Medicine and Pharmacy. The first program me is accredited and has started to be implemented in October 2021, pharmacy is expected to be implemented in October 2022.